The Development on Enhancing Life Skill Activity Based on Contemplative for Non-Formal Education Student - Rungsrisuriyachai, Boonyarat; Comesorn, Sukkaew; Jaingam, Siriwimol (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2018)
The purpose of this research was to develop the activities to enhance life skill using contemplative study for Non-formal education students. The research methodology was divided into four steps: 1) study the condition of activity management on life skill for Non-formal education students from the life enhancing project for Non-formal education from 18 centers in the lower northern Thailand and interview teachers who are dealing with the problems on activity management on life skill for Non-formal education from each 2 provincial centers in 9 provinces; 2) develop enhancing life skill activities based on contemplative for Non-formal education students by collecting data from related documents and constructing the activities based on the result from the first step and checking the appropriateness by 7 experts; 3) study the results of enhancing life skill activities based on contemplative study for Non-formal education students at Non-formal Education Center in Huay Pong Sub-district, Nongphai District, Phetchabun province from 30 people; 4) study the students’ satisfactions towards enhancing life skill activities based on contemplative study for non-formal education. The findings found that 1) the activity management to enhance life skill using contemplative study for Non-formal education students was not met with 4 facets and most of the activities enhanced the fourth skill; that is, making good relation with others with 100%, secondly, realizing and valuing in self and others with 88.88%. The second facet was making analytical decision and creative problem solving with 27.77% and the least facet was the emotional management with 5.55%. 2) The development on enhancing life skill activities based on contemplative study for Non-formal education students comprised 13 activities and activity management was appropriate at a high level. 3) The outcome of using activities to enhance life skill using contemplative study for Non-formal education students found that the life skill of Non-formal education students after joining in the activities was higher than before joining the activities significantly different at 0.05. 4) The students’ satisfactions towards the enhancing life skill activities based on contemplative study for Non-formal education overall were at a very high level.